KUALITAS PELAYANAN KANTOR PERUSAHAAN DAERAH AIR MINUM DI KELURAHAN MAMBORO BARAT KOTA PALU - irha, Sukira; Hattab, Syahruddin; Farista, Gita (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
Drinking water companies are one of the companies that produce water services to the community, but in providing services to the community there are still many problems including cloudy and yellowish water. This study aims to determine how the quality of service and efforts made at PDAM Kelurahan Mamboro Barat. This research uses a qualitative descriptive approach. This research uses Snowball sampling technique. Data collection techniques through observation, interviews and documentation. The results of this study indicate that the services provided by PDAM Mamboro Barat have not been said to be good, especially in the indicators of Service, Time and facilities. this can be seen from the completeness of inadequate infrastructure, the timeliness of opening service counters that are not on schedule by PDAM Mamboro Barat and the slow response of officers to complaints and problems experienced by customers. All forms of this problem need improvement so that in the future it can run well.